2014
DOI: 10.1159/000356913
|View full text |Cite
|
Sign up to set email alerts
|

Absence of GPR54 and TACR3 Mutations in Sporadic Cases of Idiopathic Central Precocious Puberty

Abstract: Background/Aims: Kisspeptin (KISS1)/GPR54 (KISSR) signaling complex and neurokinin B (NKB)/NKB receptor (TACR3) signaling have been proposed as an integral part of the network coordinating GnRH release. GPR54 (KISS1R) and TACR3 gene mutations have been described in cases of idiopathic hypogonadotrophic hypogonadism, while limited data exist on gain-of-function mutation in GPR54 (KISS1R) gene causing idiopathic central precocious puberty (ICPP). No data on TACR3 mutations in ICPP have been described so far. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…These findings are consistent with the data published by other groups [25,26,36,37,38,39]. Nonetheless, as we have sequenced the 4,813 OMIM genes, we are developing a further analysis to find any other genes implicated in the neuroregulation of puberty.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with the data published by other groups [25,26,36,37,38,39]. Nonetheless, as we have sequenced the 4,813 OMIM genes, we are developing a further analysis to find any other genes implicated in the neuroregulation of puberty.…”
Section: Discussionsupporting
confidence: 91%
“…Many of the other identified loci are associated with BMI or energy homeostasis (Elks et al, 2010). While GPR54 (Teles et al, 2008;Leka-Emiri et al, 2014), TACR3 (Leka-Emiri et al, 2014) and LIN28B (SilveiraNeto et al, 2012) mutations seem to be very uncommon or absent in patients with precocious puberty (PP), inactivating mutations in the makorin ring finger protein 3 (MKRN3) gene, have been recently identified in 2-3% of sporadic PP and even more frequently in familial PP (Abreu et al, 2013;Macedo et al, 2014;Schreiner et al, 2014) and result in invalidation of a so far unidentified inhibitory neuroendocrine mechanism.…”
Section: Genetic Regulation Of Pubertal Timing and Environmental Intementioning
confidence: 99%
“…Mutations or SNPs associated with CPP were initially described in KISS1 and KISS1R (7,8,9), but mutations of these genes are very rare in sporadic cases of iCPP (10). A recent whole-exome sequencing study identified mutations in the makorin RING finger 3 (MKRN3) gene in 15 individuals with iCPP (11).…”
Section: Introductionmentioning
confidence: 99%